2011
DOI: 10.1128/jcm.01884-10
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Subtypes of Poultry Clostridium perfringens Isolates Demonstrate Disease Niche Partitioning

Abstract: Clostridium perfringens is a ubiquitous and versatile pathogenic bacterium and is implicated in the etiology of the poultry diseases necrotic enteritis (NE) and poultry gangrene (PG). In this study, multilocus sequence typing was used to investigate genotypic relationships among 139 C. perfringens isolates from 74 flocks. These isolates had multiple disease, host, and environmental origins. The results indicated a polymorphic yet highly clonal population, with 79.6% of all isolates partitioning into one of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 43 publications
(68 reference statements)
2
46
0
Order By: Relevance
“…A recent MLST study examining NE and healthy bird C. perfringens isolates found that the majority of those associated with NE belonged to two phylogenetically distinct clonal groups: clonal cluster 4 (CC-4) and sequence type 31 (ST-31) (13). Based on in silico MLST analysis, CP4 and JGS4143 belong to CC-4 and ST-31, respectively (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent MLST study examining NE and healthy bird C. perfringens isolates found that the majority of those associated with NE belonged to two phylogenetically distinct clonal groups: clonal cluster 4 (CC-4) and sequence type 31 (ST-31) (13). Based on in silico MLST analysis, CP4 and JGS4143 belong to CC-4 and ST-31, respectively (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Previous pulsed-field gel electrophoresis (PFGE) analyses of NE-associated C. perfringens isolates failed to provide evidence for a relationship between subtypes from different flocks (11,12), indicating that there were numerous clonal origins of virulent strains that resulted from horizontal transfer of virulence genes. However, two recent multilocus sequence typing (MLST) studies identified two prevalent clonal groups among NE-associated isolates, thus suggesting that specific core chromosomal genes might be important for NE pathogenesis (13,14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have indicated that the C. perfringens strains that are commonly present in low numbers within the healthy gut are generally distinct from the strains that can go on to cause disease 3,4 . The origin of pathogenic strains has not yet been clarified and the mechanisms driving displacement of non-pathogenic strains by pathogenic strains are not clear but may be partly driven by bacteriocin expression by the pathogenic strains 5 .…”
mentioning
confidence: 99%